2022
DOI: 10.3390/toxics10040180
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-Head Study of Developmental Neurotoxicity and Resultant Phenotype in Rats: α-Hexabromocyclododecane versus Valproic Acid, a Recognized Model of Reference for Autism Spectrum Disorders

Abstract: Evidence is now growing that exposure to environmental pollutants during the critical early-life period of brain development may contribute to the emergence of Autism Spectrum Disorders (ASD). This study seeks to compare the developmental neurotoxicity of the α-isomer of hexabromocyclododecane (α-HBCDD), a persistent brominated flame retardant, to the valproic acid (VPA) model of ASD in rodents. Pregnant Wistar rats were divided into three groups: control, α-HBCDD (100 ng/kg/day p.o., GD0-PND21) and VPA (600 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The number and size of neurons in the MGN of Cntnap2 −/− mice has been shown to be reduced [ 140 ]. Despite increased sound-evoked activity shown by c-Fos staining, CO staining showed reduced activity in the IC, LL, and MGN in the absence of sound stimulation in VPA rats [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number and size of neurons in the MGN of Cntnap2 −/− mice has been shown to be reduced [ 140 ]. Despite increased sound-evoked activity shown by c-Fos staining, CO staining showed reduced activity in the IC, LL, and MGN in the absence of sound stimulation in VPA rats [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study that did so found the habituation rate of the N1 amplitude was lower in Fmr1 −/− mice, but only at presentation rates greater than one stimulus per second [70]. This difference in Chrna7 (18) , Cntnap2 (70) , Drd2 (42) , Mecp2 (35,86) , Wnt1 P1 Many studies with Fmr1 −/− mice have found no difference in the amplitude of the P1 peak, though a recent study using a higher number of channels found an increased P1 in Fmr1 −/− mice compared to WTs [55,60,67,130,147]. The P1 amplitude is generally not different to WTs in other ASD models, with the exception of 15q13.3 deletion mice [48,57,64,121].…”
Section: Cortical Event-related Potentialsmentioning
confidence: 96%
“…Researchers have explored its effects on fetal neural development by injecting propionic acid into pregnant mice to simulate a potential environmental factor, i.e., drug exposure, during pregnancy ( 55 ). Propionic acid is an antiepileptic drug that has been found to be associated with ASD risk.…”
Section: Discussionmentioning
confidence: 99%